THE EUROPEAN INVESTIGATION ORDER IN CRIMINAL MATTERS - GROUNDS FOR NON-RECOGNITION OR NON-EXECUTION - Daniela DEDIU (Challenges of the Knowledge Society)
The European Investigation Order (EIO) is the newest mechanism for judicial cooperation in criminal matters. This instrument was laid out in the Directive 2014/41/EU of the European Parliament and of the Council of 3 April 2014 and was transposed into the Romanian legislation through the most recent changes of the Law nr. 302/2004 concerning international judicial cooperation in criminal matters The main goal was the introduction of a single instrument for the gathering of evidence between EU Member States in cases with a cross-border dimension. Also, the European Investigation Order is the most recent application of the principle of mutual recognition of judgments and judicial decisions, which is, since the Tampere European Council the cornerstone of judicial cooperation in criminal matters within the Union. Starting with an analysis of the principle of mutual recognition, this paper presents the grounds for non-recognition or non-execution provided both by the Directive regarding the European Investigation Order and Romanian national legislation. Non-recognition and non-execution grounds of a European Investigation Order are either the classic reasons for the cooperation instruments (ne bis in idem principle), but are also noticed through elements of novelty as the ones based on respecting the fundamental rights, aspect that represents an important step in the cooperation matter and shows the ECJ jurisprudence tendency.